Investigating cardiac energetics in heart failure. - Lygate, C; Schneider, J; Neubauer, S (2013)
The energetic requirements of the heart are, weight for weight, higher than for any other organ. The heart provides non-stop function for a lifetime, while maintaining energy in reserve in order to respond to increased demand. This demand is met by continuously recycling a relatively small pool of ATP, with the creatine kinase (CK) system acting as a spatial and temporal buffer. In the failing heart, key components of this system are downregulated, but whether these energetic changes are biomarkers or drivers of dysfunction and whether they represent therapeutic targets are the subjects of ongoing research. Key methodologies are now becoming available in vivo to help address these questions in mouse models, such as (31)P magnetic resonance spectroscopy to detect high-energy phosphates and (1)H magnetic resonance spectroscopy to detect total creatine. This report briefly discusses the challenges involved in using these technologies, the application and pitfalls of murine surgical models of heart failure, and how this has contributed to our understanding of pathophysiology in recent years.